The Evolution of Arbitration Law in Islamic Republic of Pakistan: Historical Context and Future Directions. - Munir, Yasir (AL-IDRAK JOURNAL, 2024)
The British Arbitration Act 1940 was extended to and implemented in Pakistan on the date of independence. August 14, 1947. Methods such as arbitration are preferred since they are efficient legal techniques that are not as costly, and the public has trust in arbitrators. The Arbitration Act of 1940 is practiced Mostly in urban territories when court execution of arbitral decisions is needed, however, Jirga as well as Panchayat are perhaps recognizable conventional techniques that persisted in rural zones. Among various organizations of urban arbitration. As the New York Convention of 1958, the structure of arbitration entails the Recognition and Enforcement Act 2011 conducted internationally. There are calls for the adoption of the UNCITRAL MODEL LAW 1985 apart from calling for the amendment of the Arbitration ACT 1940 to be by international standards and Islamic Sharia, yet this has not been operationalized. Terms of agreement can be used in the arbitration process although written agreement is often refrained in rural areas. Currently, arbitrators work under should act by the provisions of the Arbitration Act 1940 unless provided otherwise. In the same year April 2023, to enhance the domestic arbitration position in Pakistan and to align with the UNCITRAL Model Law, the Chief Justice of Pakistan created the Arbitration Law Review Committee (ALRC). Based on the Indian Arbitration Act of 1996 and other foreign forms, the proposed Arbitration Bill would help increase arbitrations and reduce the legal system’s interference. It aims at enhancing the arbitration legal structure of Pakistan by creating a distinction between domestic and international arbitral proceeding, specificity of the rules regarding the selection of arbitrators, interim measures and award execution.